A multicenter cohort study of early complications after cranioplasty: results of the german cranial reconstruction registry - Sauvigny, Thomas; Giese, Henrik; Höhne, Julius; Schebesch, Karl-Michael; Henker, Christian; Strauss, Andreas; Beseoglu, Kerim; Spreckelsen, Niklas von; Hampl, Jürgen; Walter, Jan; Ewald, Christian; Krigers, Aleksandrs; et al. (Journal of neurosurgery, 2022)
OBJECTIVE Cranioplasty (CP) is a crucial procedure after decompressive craniectomy and has a significant impact on neurological improvement. Although CP is considered a standard neurosurgical procedure, inconsistent data on surgery-related complications after CP are available. To address this topic, the authors analyzed 502 patients in a prospective multicenter database (German Cranial Reconstruction Registry) with regard to early surgery-related complications. METHODS Early complications within 30 days, medical history, mortality rates, and neurological outcome at discharge according to the modified Rankin Scale (mRS) were evaluated. The primary endpoint was death or surgical revision within the first 30 days after CP. Independent factors for the occurrence of complications with or without surgical revision were identified using a logistic regression model. RESULTS Traumatic brain injury (TBI) and ischemic stroke were the most common underlying diagnoses that required CP. In 230 patients (45.8%), an autologous bone flap was utilized for CP; the most common engineered materials were titanium (80 patients [15.9%]), polyetheretherketone (57 [11.4%]), and polymethylmethacrylate (57 [11.4%]). Surgical revision was necessary in 45 patients (9.0%), and the overall mortality rate was 0.8% (4 patients). The cause of death was related to ischemia in 2 patients, diffuse intraparenchymal hemorrhage in 1 patient, and cardiac complications in 1 patient. The most frequent causes of surgical revision were epidural hematoma (40.0% of all revisions), new hydrocephalus (22.0%), and subdural hematoma (13.3%). Preoperatively increased mRS score (OR 1.46, 95% CI 1.08-1.97, p = 0.014) and American Society of Anesthesiologists Physical Status Classification System score (OR 2.89, 95% CI 1.42-5.89, p = 0.003) were independent predictors of surgical revision. Ischemic stroke, as the underlying diagnosis, was associated with a minor rate of revisions compared with TBI (OR 0.18, 95% CI 0.06-0.57, p = 0.004). CONCLUSIONS The authors have presented class II evidence-based data on surgery-related complications after CP and have identified specific preexisting risk factors. These results may provide additional guidance for optimized treatment of these patients.
Online veröffentlicht am 17. Dezember 2021
Gesehen am 09.02.2023